Industrial water demand analysis in the Middle Olifants sub-basin of South Africa: The case of mining - Teresa Linz; Daniel W. Tsegai (University of Bonn, Center for Development Research (ZEF), 2009)
This paper seeks to determine water demand of the mining sector in the Middle Olifants sub-basin of South Africa. Despite the growing economic importance of mining in the area, only little is known about its water demand and the role of water in the mines extraction process. By means of econometric estimation water price elasticities as well as substitution possibilities between water and other inputs are derived to analyze the response of mines to changes in water tariffs. Using primary data, a translog cost function is estimated for five mines operating in the area. Cost share equations of each input are specified and estimated using Seemingly Unrelated Regression (SUR) method. The mean cost share of water for all five mines, with around 1%, is relatively small, reflecting the low water tariff and results show industrial water demand to be inelastic. Nevertheless, with water price elasticity values ranging from -0.77 to -0.95 for the five mines, there is a potential to influence water use patterns through higher tariffs. As mines are water intensive industries, possible water savings owing to raised water tariffs should not be neglected. Water intake is found to be a substitute for labor and capital for most of the mines, implying that capital investments in water saving technologies might be an alternative means to reduce water intake of the mining sector. – – Die vorliegende Studie untersucht die industrielle Wassernachfrage im Bergbau im Wassermanagement Gebiet des Mittleren Olifants in Südafrika. Trotz der wachsenden Bedeutung des Bergwerksektors im Untersuchungsgebiet, ist nur wenig über seine Wassernachfrage sowie die Rolle des Wassers im Abbauprozess bekannt. Mit Hilfe eines ökonometrischen Ansatzes werden Wasserpreiselastizitäten sowie Substitutionsmöglichkeiten zwischen Wasser und anderen Produktionsfaktoren berechnet, um Veränderungen der Wassernachfrage einzelner Bergwerke als Antwort auf unterschiedliche Wasserpreise zu analysieren. Eine translogarithmische Kostenfunktion wird mit primären monatlichen Zeitreihendaten für fünf verschiedene Minen geschätzt. Für die einzelnen Produktionsfaktoren werden Gleichungen mit den jeweiligen Kostenanteilen (n=5) als abhängige Variablen mit der Seemingly-Unrelated Regression (SUR) Methode geschätzt. Die durchschnittlichen Wasserkosten der Datenreihen sind mit einem Anteil von circa 1% der Gesamtkosten sehr gering und Ergebnisse zeigen eine relativ unelastische Wassernachfrage. Mit Wasserpreiselastizitäten zwischen -0.77 und -0.95 bestehen dennoch Möglichkeiten die Wassernachfrage mit Hilfe höherer Wasserpreise zu beeinflussen. Da der Bergwerksektor eine sehr wasserintensive Industrie darstellt, sollten resultierende mögliche Wassereinsparungen nicht vernachlässigt werden. Bei einem Großteil der untersuchten Bergwerke ist Wasser ein Substitut für Arbeit und Kapital, was bedeutet, dass Investitionen in wassersparenden Technologien helfen würden, die Wassernachfrage im Bergbau zu reduzieren.
Keywords: 330; Wasser; Nachfrage; Bergbau; Kostenfunktion; Faktorsubstitution; Wasserpreis; Preiselastizität; Schätzung; Südafrika